Decoding the diagnostic landscape of adnexal masses: a retrospective observational study at a tertiary care centre assessing the efficacy of the RMI-2 index - Shahu, Sheetal; Asrani, Manisha; Raithatha, Nitin; Parmar, Saurabh; Vaishnav, Smruti; Bhattacharjee, Rumi (International Journal Of Community Medicine And Public Health, 2024)
Background: This study aimed to determine the utility of RMI 2 in distinguishing benign and malignant adnexal masses in low-income countries. Methods: For the purpose of this retrospective observational study, relevant data from patients who attended a tertiary care institution in central Gujarat between June 2020 and June 2022 were obtained from the Medical Records Department (MRD). Ultrasound and biochemical parameters along with epidemiological factors were identified and an RMI 2 score was calculated followed by statistical analysis. Results: Twenty-five (37.87%) of the sixty-six instances that were investigated were benign, two (3.03%) were borderline, and thirty-nine (59.09%), were malignant. Using RMI 2 at the traditional cut-off value of 250, results showed a sensitivity of 85.2% (95 %; CI=68.9-95.05), a specificity of 66.6% (95 %; CI=47.1-82.7 %), a positive predictive value of 74.36%, and a negative predictive value of 80.0 %. The ROC showed an AUC of 0.68 (CI=0.5-0.7) with a standard error of 0.07 (p=0.009). Conclusions: With a cut-off point of 250, RMI 2 was able to identify malignant masses with an 85.2% sensitivity and 66.6% specificity to enable timely referral to more advanced institutions for improved management in resource-constrained settings where its affordability and user-friendliness are favourable.